Pega, mata, lincha! Um estudo sobre linchamentos no Amazonas - Porto, Karolline De Andrade (2021)
The thesis investigates the phenomenon of lynching in the state of Amazonas by examining four incidents. Lynching is common in that state, both in the city and in the countryside. A descriptive research using a qualitative methodology was designed to characterize the acts, with documentary and bibliographic backing. Official procedures and reports on cases filed with the state, as well as data gathered from social media and a review of books and scientific journals on the subject, were examined. The first chapter included a survey of the lynching bibliographies based on the work of ten authors, as well as an exploration of the themes of violence, including enslavement and punishment of black people. In the situations to which we had access, race was a prominent factor. This movement allowed for the correlation of the settings identified in the examples initially chosen with the base authors' understandings, as well as the observation of the link between State penalties and civilian punishments/tortures. As a result, some practices were found to be remarkably similar to aggressions against LGBTQIA+ people, indicating that more research is needed to determine the point at which they converge with aggressions in the lynching studied thus far, highlighting the powerful influence of religious discourses in the spread of disrespect and obstruction of LGBT rights. The qualitative data collected, the methodology used, and the path taken to obtain them are presented in the following chapter, as well as the one that integrates the State's Administrative and Judicial Systems, which is divided into a section on lynching in general and another on crimes and violence against LGBTQIA+ people. The final chapter examines lynching cases, two of which occurred in Manaus and two in the cities of Borba and Novo Aripuanã/AM. Those involved in these lynching incidents have been designated by the community as perpetrators of a crime that disrupted the area's normalcy, including black/brown individuals, LGBTQIA+ persons, and a woman (crimes against sexual dignity, against life, property, and public safety). This study found that victims of lynching are more likely to experience gender and racial violence, and that such reactions from the public feedback into a punitive continuum with violent institutional practices, without overlooking the rationality that drives lynching and is reaffirmed by motivations for private, immediate justice, as well as the moralities that prevail.